Primary squamous cell carcinoma of the pancreas: an update on a rare neoplasm from the SEER database - Ford, Jacob A.; Bhatt, Arjun; Kim, Rachel C.; Larkins, Michael; Burke, Aidan M. (Frontiers in Oncology, 2023)
Introduction Pancreatic squamous cell carcinoma is a rare type of pancreatic cancer of ductal origin, composing an estimated 0.5 - 5% of pancreatic ductal malignancies. As a result, epidemiology, treatment options, and associated outcomes are poorly understood and understudied. Our aim was two-fold: to evaluate demographic trends and analyze overall survival (OS) associated with different treatment modalities for this rare malignancy. Methods Patients with pancreatic squamous cell carcinoma diagnosed between 1992 and 2019 were eligible and reviewed utilizing the Surveillance, Epidemiology, and End Results Registry (SEER) database. Data was analyzed using SPSS and python packages lifelines and pandas. Variables of interest included stage at diagnosis as well as the receipt of surgery, radiotherapy, and/or chemotherapy. Five-year OS curves were analyzed using Kaplan-Meier probability stratified by treatment modality. Results Of 342 cases of pancreatic squamous cell carcinoma, 170 (49.7%) were females and 172 (50.3%) were males. 72 (21.1%) of patients received radiotherapy, 123 (35.9%) patients received chemotherapy, and 47 (13.7%) received surgery. Patients who were diagnosed under the age of 50 had prolonged survival time compared to those diagnosed over the age of 50 (12 vs 8 months, respectively, p < 0.001). This trend was evident despite the lack of a significant association between age at diagnosis and presence of metastases (p = 0.524). The median OS was 3 months for the entire cohort and there was a significant difference in median survival time noted across treatment modalities: OS was prolonged in those receiving surgery compared to those receiving chemotherapy or radiotherapy alone (30 vs 2 months, respectively, (p<0.001)). Receipt of radiotherapy was not associated with a significant difference in OS compared to those who did not receive radiotherapy. Conclusion Pancreatic squamous cell carcinoma is a rare subtype of pancreatic cancer and typically portends a poor prognosis. As demonstrated by our study, surgery offers prolonged overall survival compared to other treatment modalities. Age at diagnosis and presence of metastatic disease are also important prognostic factors likely related to patients‘ ability to tolerate surgery or physician willingness to offer surgery. Given the importance of surgery on outcomes, it may be reasonable to offer it in the oligometastatic setting in patients who are otherwise a good candidate. Future research on larger cohorts is warranted to investigate the role that modality selection plays in overall survival rates in this understudied malignancy.